2012
DOI: 10.1038/bjc.2012.202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of circulating CK-19mRNA-positive tumour cells before front-line treatment in patients with metastatic breast cancer

Abstract: Background:To investigate the clinical relevance of CK-19mRNA-positive circulating tumour cells (CTCs) detected before the initiation of front-line treatment in patients with metastatic breast cancer (MBC).Methods:The presence of CTCs was detected in 298 patients with MBC using a real-time PCR (RT-PCR assay. In 44 patients, the detection of CTCs was evaluated by both the CellSearch and the RT-PCR assay. Interaction with known prognostic factors and association of CTCs with clinical outcome were investigated.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…Increased numbers of CTC before the second cycle of therapy was an early predictive marker of poor PFS and OS, and could be used to monitor treatment benefit, whereas CTC decrease under treatment was stronger with targeted therapy (14). The detection of CTCs in patients with MBC before front-line therapy could define a subgroup of patients with dismal clinical outcome (15). A recent meta-analysis clearly indicated that the detection of CTCs is a reliable prognostic factor in patients with earlystage and MBC (16), whereas numerous ongoing trials evaluate CTCs as markers for early prediction of treatment efficacy (17).…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of CTC before the second cycle of therapy was an early predictive marker of poor PFS and OS, and could be used to monitor treatment benefit, whereas CTC decrease under treatment was stronger with targeted therapy (14). The detection of CTCs in patients with MBC before front-line therapy could define a subgroup of patients with dismal clinical outcome (15). A recent meta-analysis clearly indicated that the detection of CTCs is a reliable prognostic factor in patients with earlystage and MBC (16), whereas numerous ongoing trials evaluate CTCs as markers for early prediction of treatment efficacy (17).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of tumor cells in the peripheral blood (circulating tumor cells; CTCs) and bone marrow aspirates (disseminated tumor cells; DTCs) has been described in cancer patients567891011 and has been shown to be associated with shorter progression free (PFS) and overall (OS) survival in various tumor types, including SCLC121314151617181920. In SCLC patients, the detection of CTCs before the initiation of systemic treatment as well as post-treatment and at the time of clinical relapse has been shown to be associated with a worse overall survival1517181920.…”
mentioning
confidence: 99%
“…Specifically, the detection of CK19 mRNA-positive cells either before the initiation or after the completion of adjuvant chemotherapy as well as during follow-up, was predictive of poor clinical outcome in patients with early stage breast cancer [7, 8, 20]. In the metastatic setting, the presence of CK19 mRNA-positive cells before the initiation of front-line chemotherapy identifies a group of patients with dismal prognosis [21]. …”
Section: Introductionmentioning
confidence: 99%